2019
DOI: 10.1073/pnas.1900308116
|View full text |Cite
|
Sign up to set email alerts
|

A SWI/SNF subunit regulates chromosomal dissociation of structural maintenance complex 5 during DNA repair in plant cells

Abstract: DNA damage decreases genome stability and alters genetic information in all organisms. Conserved protein complexes have been evolved for DNA repair in eukaryotes, such as the structural maintenance complex 5/6 (SMC5/6), a chromosomal ATPase involved in DNA double-strand break (DSB) repair. Several factors have been identified for recruitment of SMC5/6 to DSBs, but this complex is also associated with chromosomes under normal conditions; how SMC5/6 dissociates from its original location and moves to DSB sites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In the genome of the model plant, Arabidopsis thaliana , there are four Swi3 proteins, including SWI3A/3B/3C/3D ( Sarnowski et al, 2005 ). Results of a genetic analysis indicate that these components play essential roles in regulating multiple growth and developmental processes ( Sarnowski et al, 2005 ; Han et al, 2018 ; Jiang et al, 2019 ; Yang et al, 2020 ). SWI3A, SWI3B, and SWI3C proteins interact with one another, whereas SWI3D only interacts with SWI3B ( Sarnowski et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the genome of the model plant, Arabidopsis thaliana , there are four Swi3 proteins, including SWI3A/3B/3C/3D ( Sarnowski et al, 2005 ). Results of a genetic analysis indicate that these components play essential roles in regulating multiple growth and developmental processes ( Sarnowski et al, 2005 ; Han et al, 2018 ; Jiang et al, 2019 ; Yang et al, 2020 ). SWI3A, SWI3B, and SWI3C proteins interact with one another, whereas SWI3D only interacts with SWI3B ( Sarnowski et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have shown that SMC5/6 also negatively regulates cell cycle progression by inhibiting E2F transcription factors (Wang et al , 2018). Recent studies in Arabidopsis revealed that the recruitment of SMC5/6 is dependent on the IDN2–CDC5–ADA2b module (Lai et al , 2018; Jiang et al , 2019, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro pull-down and in vivo co-IP assays For the in vitro pull-down assay, the indicated proteins were produced in Escherichia coli BL21(DE3), and the assay was performed as previously described (Jiang et al, 2019). For co-IP, constructs encoding the indicated proteins were expressed in Arabidopsis or N. benthamiana leaves, and the assay was conducted as previously described (Niu et al, 2019).…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%